Effectiveness and repeatability of eye-tracking-based test in strabismus measurement of children. (19th May 2022) - Zou, Leilei; Tian, Tian; Wygnanski-Jaffe, Tamara; Yehezkel, Oren; Wang, Shu; Moshkovitz, Avital; Sun, Xinghuai; Liu, Hong; Liu, Rui
ABSTRACT: Objectives: To assess the effectiveness of an eye-tracking-based test (ETBT) to measure eye deviation angle vs. a manual prism alternating cover test (PACT) in children with strabismus. Design: The prospective, masked, cross-sectional study included 95 children aged 1.8 years and older. Eye deviation was tested twice by each of ETBT and PACT. Each subject underwent four strabismus measurements, two by the ETBT and two by PACT. In each test, subjects were fixated on accommodative targets at 50 cm, with habitual optical correction allowed. Masked examiners compared the manual PACT results with those of the ETBT. Results: There was a high correlation (about 90%) between the ETBT and PACT. Repeatability of ETBT was higher than that of PACT (correlation coefficients of 0.99 and 0.91 respectively, p < .002). Age, strabismus type, and eye deviation measurement did not affect repeatability of ETBT. However, in PACT, results could not be correlated between the two examiners when the deviation was larger than 40 prism diopters. Conclusions: The ETBT was effective in measuring eye deviation in children as young as 1.8 years. The ETBT showed higher repeatability compared to PACT.